MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI MELALUI PENERAPAN METODE DISKURSUS MULTY REPRECENTACY (DMR) - Rita Patonah (Faktor Jurnal Ilmiah Kependidikan, 2019)
Learning outcomes are the most important part of learning. Each learning process of its success is measured by how much learning outcomes that have been achieved by learners.The formulation of this research problem is : 1) Are there improvements in student learning outcomes using the Discourse Multy Reprecentacy (DMR) method on pretest and posttest measurements? 2) Are there improvements in student learning outcomes using lecture methods on pretest and posttest measurement? 3) Is there any influence of students' learning outcomes using the method of Discourse Multy Reprecentacy (DMR) with lecture method?This study aims to determine: 1) Improvement of learning outcomes of learners using the method of Discourse Multy Reprecentacy (DMR) on pretest and final measurement (posttest); 2) Improved learning outcomes of learners using lecture methods on pretest and final measurements (posttest); 3) Effect of learning outcomes of learners using the method of Discourse Multy Reprecentacy (DMR) with lecture method. The research method used is experimental research method Quasi Experimental Design type Desgin Non Equivalent Control Group Design.The results showed that : 1) There is an increase in learning outcomes of learners using multy reprecentacy (DMR) learning method; 2) There is an increase in learning outcomes of learners who get the lecture method; 3) There is a significant effect of learning outcomes of learners using multy reprecentacy (DMR) method of discourse rather than using lecture method on final measurement (posttest).